(3GdeNJGQ aj GdWHs - (3Ydj Hf CMeO Hf Ydj Hf YHO GdefYe, CHh GdMSf, GdegPH, GdeYQha HGHf gHd,J (B610 (3g` s ((3eMeO Hf CMeO GHf eMeO Hf jMji s)
(3ChdgG (B:s
(3CeG HYO aEf TQa GdYdhe hGdUfGFY HMSH TQa ehVhYgG hdeG cGfJ GdUfGYI GdWHjI fGXQI aj HOf GdEfSGf UGQJ ef CfaS GdUfGFY s
(3BNQgG (B:s
(3hdfNJe GdBf GdcdGe aj GdCUhd GdcdjI aj GdWH , hdfCNP aj PcQ GdCOhjI GdeaQOI hGdeQcHI hdfHSW GdcdGe ajgG , dCfgG gj GdBdI GdeYfjI aj oebheI GdCeQGV s
(3HGdhQbI GdChdi JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B256 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B21s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B220 s
Keywords: (3GdWHs